2022
DOI: 10.6004/jnccn.2022.7042
|View full text |Cite
|
Sign up to set email alerts
|

Incident Cardiovascular Diseases Among Survivors of High-Risk Stage II–III Colorectal Cancer: A Cluster-Wide Cohort Study

Abstract: Background: The incidence and survival of colorectal cancer (CRC) are increasing. There is an increasing number of long-term survivors, many of whom are elderly and have comorbidities. We conducted a population-based study in Hong Kong to assess the long-term cardiovascular disease (CVD) incidence associated with adjuvant fluoropyrimidine-based chemotherapy among CRC survivors. Patients and Methods: Using the population-based electronic medical database of Hong Kong, we identified adults who were diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The findings highlight the importance of age, LDL-C, and serum CRP level as independent risk factors for cardiovascular complications in such patients. The incidence rate was found to be 15.8%, which is lower than the rate reported in a previous study [33]. This difference may be due to differences in patient characteristics and in the duration of follow-up.…”
Section: Cardiovascular Complications In Crc Patientscontrasting
confidence: 74%
“…The findings highlight the importance of age, LDL-C, and serum CRP level as independent risk factors for cardiovascular complications in such patients. The incidence rate was found to be 15.8%, which is lower than the rate reported in a previous study [33]. This difference may be due to differences in patient characteristics and in the duration of follow-up.…”
Section: Cardiovascular Complications In Crc Patientscontrasting
confidence: 74%
“…For illustration, Kelly et al reported the increased risk of new cardiovascular diseases and congestive heart failure in elderly CRC patients, reminding that elderly patients with a history of chemotherapy should be closely monitored in clinical work [14] . A population-based study in South Korea also noted that 5-FU chemotherapy for CRC patients was associated with an increased risk of CVD [15] . Previous studies only discussed the incidence of CVD in chemotherapy patients, but rarely compared the prognosis of patients.…”
Section: Introductionmentioning
confidence: 94%
“…In the United States, research on disparities in common cancers with elevated cardiovascular risk, including lung, 66 , 67 , 68 colorectal, 69 , 70 , 71 , 72 bladder, 73 , 74 endometrial, 75 , 76 and hematologic malignancies, 77 , 78 , 79 , 80 , 81 is still underway. Understanding the shared risk factors between these cancers and CVDs, combined with recent treatment advancements, underscores the need to address social disparities in this space.…”
Section: Cardiovascular Risk In Higher Prevalence Cancers In the Usmentioning
confidence: 99%